O aprendizado de uma tarefa de navegação espacial altera os níveis de GABA no hipocampo de camundongos SWISS - Isabela Cristina Campos de Sena (2015)
Many efforts have been made to understand the neurobiological basis of memory and learning. Among the animal models that have been used to achieve these objectives,mice represent an important alternative for studying some of the biological processes related to behavioral aspects or associated with nervous system dysfunctions. Using Swiss mice, the objectives of the present study were: (i) evaluate the performance - learning and memory - in a spatial navigation task in the Shallow Water Maze (SWM), (ii) measure the concentrations of GABA and glutamate in the hippocampus, and (iii) first evaluate the correlations between the neurochemical data and the behavioral parameters and, second, to evaluate the correlation between the neurochemical parameters themselves. We used 46 three-month-old Swiss mice, divided into three groups: (i) Control Group: animals that underwent neither the cognitive task nor exposure to SWM, (ii) Control Activity Group: animals were exposed to the SWM without exposure to the cognitive task, and (iii) Learning Group: animals that were submitted to the cognitive task in the SWM. The behavioral test consisted of seven consecutive daily sessions with four trials per session. After the fifth session the animals were submitted to the Probe Trail and after the last training session, animals were euthanized and their hippocampus was dissected and separated for GABA and glutamate assays using the HPLC method. There was significant training effect, indicating that the animals of the "learning" group were able to learn the task. There was also a significant treatment effect on the preference for the target quadrant, confirming that the animals used extra-maze spatial cue for exiting the SWM. In addition, the cognitive exercise of solving the spatial navigation task affected (increase) the concentrations of GABA in the hippocampus, which effect was significant related to animal behavioral performance in the two first training sessions. The experimental conditions used in the present study were suitable for assessing spatial cognitive learning using mice as an animal model. Moreover, we show for the first time that the acquisition of a spatial task involves changes in GABA contents in the hippocampus.